OzDES multi-object fibre spectroscopy for the Dark Energy Survey: results and second data release. Issue 1 (30th May 2020) - Lidman, C; Tucker, B E; Davis, T M; Uddin, S A; Asorey, J; Bolejko, K; Brout, D; Calcino, J; Carollo, D; Carr, A; Childress, M; Hoormann, J K; et al.
ABSTRACT: We present a description of the Australian Dark Energy Survey (OzDES) and summarize the results from its 6 years of operations. Using the 2dF fibre positioner and AAOmega spectrograph on the 3.9-m Anglo-Australian Telescope, OzDES has monitored 771 active galactic nuclei, classified hundreds of supernovae, and obtained redshifts for thousands of galaxies that hosted a transient within the 10 deep fields of the Dark Energy Survey. We also present the second OzDES data release, containing the redshifts of almost 30 000 sources, some as faint as r AB  = 24 mag, and 375 000 individual spectra. These data, in combination with the time-series photometry from the Dark Energy Survey, will be used to measure the expansion history of the Universe out to z ∼ 1.2 and the masses of hundreds of black holes out to z ∼ 4. OzDES is a template for future surveys that combine simultaneous monitoring of targets with wide-field imaging cameras and wide-field multi-object spectrographs.